IMPLEMENTASI SISTEM AKUNTANSI DAN PELAPORAN KEUANGAN ACCRUAL BASED DI SEKTOR PUBLIK - Ismawati, Kun (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2014)
Accrual accounting implementation in public sector has been a hot issue for recent decades. Many countries in the world have choose to implement accrual accounting and financial reporting as their financial management reform. This phenomenon has been debated spread away in public management and education literatures. These debate relate on the implementation and the impact of implementation in financial government governance. This article gives a little overview of accrual accounting implementation in Indonesia, mirrors from accounting and financial reporting implementation of other countries in Indonesia has implementing this system. All the legislations has designed to regulate implementing efforts. We hope that in 2015 Indonesia will be able to implement it completely. Keywords: accrual accounting and financial reporting, public sector, implementation